EVALUATION OF STRESS-STRAIN STATE OF ROCK MASS - R. A. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. A new method of determining the stress-strain state of the rocks without dropping its individual parts on the basis of combination of observations of the dynamics of piezometric level in special hydrogeological wells of pre-planned network and by the change in the diameter of wells measured by photo elastic sensors is proposed.With the beginning of the formation of the stress-strain state of the geological environment, the chaotic structure of hydro-geodynamic field(HGD-field) goes into the abnormal condition of a certain form, in accordance with the geometric shape and sizes of the geological structure. Closed lines of equal abnormal values of piezometric levels form geometric circular structures in the Central parts of which are observed their most anomalous values corresponding to the greatest extent of stressstrain state of rock massif. Within abnormal (disturbed) HGD-field is carried out the measurement of the diameters of the wells, fixed by photoelastic sensors which clarify the concrete stress-strain plot (voltages source) of the rock massif. Well drilled for measuring by photoelastic sensors of changes in their diameters, are arranged in the rock massif in a staggered manner, and the special hydrogeological well, drilled up to an isolated water system for the registration of anomalous (perturbed) HGD-field are locatedin two mutually perpendicular profiles, taking into account the geometric shape of the monitored rock mass. The combination of observations according to a pre-planned network of piezometers and wells with photoelastic sensors will allow to get a more accurate picture of the stress-strain state of the investigated deposits of rock without pass of its separate parts.